Deciphering the circadian rhythm in colorectal cancer: a bibliometric analysis of research landscape and trends - Chen, Linzi; Wang, Zhongjie; Xiao, Ningkun; Liu, Jinhui; Tao, Yuhan; Zhang, Sifang (Frontiers in Oncology, 2025)
IntroductionColorectal cancer (CRC) is a leading cause of global cancer mortality, increasingly linked to circadian rhythm disruption—a critical yet underexplored driver of tumorigenesis.MethodsThis bibliometric analysis evaluates 374 publications from the Web of Science Core Collection (1999–2024) using VOSviewer, CiteSpace, and Bibliometrix to map global research trends.ResultsAnnual publications surged post-2016, peaking in 2021, reflecting intensified focus on circadian-CRC interactions. The United States led in output (122 publications, H-index 46), followed by France (76 publications) and China (49 publications), with the Netherlands achieving the highest citation impact (88.06 citations per publication). French institutions, notably Assistance Publique–Hôpitaux de Paris (APHP), dominated translational research, while foundational studies by Levi et al. on chronomodulated chemotherapy remained pivotal. Keyword analysis identified “circadian rhythm” and “colorectal cancer” as core themes, with “inflammation” and “inflammatory bowel disease” showing significant citation bursts post-2014. Co-citation networks bridged molecular chronobiology (Science, PNAS) and clinical oncology (Cancer Research), though mechanistic studies prioritized clock genes (e.g., BMAL1, PER2) over environmental disruptors. Clinically, aligning chemotherapy with circadian rhythms reduced severe toxicity by 40% in metastatic CRC, yet gaps persist in biomarker validation and monitoring tools. Epidemiologically, shift workers faced a 20–30% elevated CRC risk, correlating with PER2 silencing in 45% of tumors and NF-κB/STAT3 pathway activation.DiscussionFuture research should integrate AI-driven circadian profiling, global collaboration, and trials targeting circadian-immune-metabolic axes to advance precision chronotherapy. This study underscores circadian biology as a cornerstone of CRC management, advocating strategies that harmonize molecular insights with ecological relevance to improve outcomes.